2010
DOI: 10.1002/adsc.201000269
|View full text |Cite
|
Sign up to set email alerts
|

Iron and Copper Salts in the Synthesis of Benzo[b]furans

Abstract: Intramolecular C À O bond forming reactions of aryl 2-bromobenzyl ketones lead to benzo [b]furans. The cyclizations can be catalyzed by 10 mol% of iron trichloride (of 98% or of 99.995% purity) or sub-mol% quantities of copper(II) chloride (of 99.995% purity).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 79 publications
0
19
0
Order By: Relevance
“…To our delight, most of the tested systems worked well with 0.005 mol% of CuI as the catalyst, giving the desired products (3) in moderate to good yields (49-91%, Table 3, entries [1][2][3][4][5][6][7][8]. For example, the 2-iodo-4-methylbenzenamine (1b) results in the desired products in yields of 71-76% (Table 3, entries 1-3).…”
Section: Scope Of the Reaction Catalyzed By Cui At Ppm Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…To our delight, most of the tested systems worked well with 0.005 mol% of CuI as the catalyst, giving the desired products (3) in moderate to good yields (49-91%, Table 3, entries [1][2][3][4][5][6][7][8]. For example, the 2-iodo-4-methylbenzenamine (1b) results in the desired products in yields of 71-76% (Table 3, entries 1-3).…”
Section: Scope Of the Reaction Catalyzed By Cui At Ppm Levelmentioning
confidence: 99%
“…[8] They found that even 0.0088 mol% of CuCl 2 catalyst is sufficient to provide benzo[b]furans in moderate yields. [8] With the use of copper/DMEDA (dimethylethylenediamine) at sub-mol% levels, Zuidema and Bolm [9] further broadened the reaction scope to Castro-Stephens coupling, the case of which is a striking example for ligand-accelerated catalysis. Very recently, a similar result was also found in the copper-catalyzed cross-coupling reaction of pyrazole and iodobenzene.…”
Section: Introductionmentioning
confidence: 99%
“…2‐ p ‐Tolylbenzofuran ( 7 )23: 4‐Methylbenzenesulfonyl chloride (0.248 g, 1.3 mmol) and benzofuran (0.118 g, 1 mmol) affords 8 in 89 % (0.185 g) yield. 1 H NMR (400 MHz, CDCl 3 ): δ =7.79 (d, J =7.8 Hz, 2 H), 7.60 (d, J =8.0 Hz, 1 H), 7.55 (d, J =7.8 Hz, 2 H), 7.52 (d, J =8.0 Hz, 1 H), 7.30 (t, J =7.8 Hz, 1 H), 7.25 (t, J =7.8 Hz, 1 H), 6.99 (s, 1 H), 2.43 ppm (s, 3 H).…”
Section: Methodsmentioning
confidence: 99%
“…2‐(4‐ tert ‐Butylphenyl)benzofuran (3c): 25 Yield: >99%; white powder; mp 127–129 °C; 1 H NMR (300 Hz, CDCl 3 ): δ =7.85 (d, J= 8.5 Hz, 2 H), 7.61 (d, J= 7.7 Hz, 1 H), 7.56 (d, J= 8.1 Hz, 1 H), 7.51 (d, J= 8.5 Hz, 2 H), 7.33–7.25 (m, 2 H), 7.02 (s, 1 H), 1.41 (s, 9 H); 13 C NMR (75.4 MHz, CDCl 3 ): δ =156.2, 154.9, 151.8, 129.4, 127.8, 125.7, 124.8, 124.0, 122.9, 120.8, 111.1, 100.7, 34.8, 31.3; MS: m / z (%)=251 (M + , 100), 250 (80); HR‐MS: m/z =251.1444, calcd. for C 18 H 19 O: 251.1436.…”
Section: Methodsmentioning
confidence: 99%